PENYULUHAN LITERASI DIGITAL BAGI SISWA SMP ISLAM PLUS AT-THOLIBIN - Dwi Wahyudi; Radinal Fadli (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The advancement of digital technology influences education, yet junior high school students often lack adequate digital literacy, making them vulnerable to hoaxes, cyberbullying, and data security issues. To address this, a digital literacy workshop was conducted at SMP Islam Plus At-Tholibin, Lampung Tengah, involving 150 participants and a purposive sample of 17 students. The program applied an interactive lecture method covering digital literacy concepts, communication ethics, security, and skills in distinguishing facts from hoaxes. Pretest–posttest evaluation showed an increase in the average score from 65.88 to 82.94, with an N-Gain of 0.50 (medium category). Six students achieved a high category, seven medium, and four low. These findings confirm that the workshop effectively improved students’ understanding, although greater emphasis is still needed on digital security.